2004
DOI: 10.1016/j.jtcvs.2003.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Management of infants with large, unrepaired ventricular septal defects and respiratory infection requiring mechanical ventilation

Abstract: Corrective cardiac surgery for selected critically ill infants with large ventricular septal defects, severe malnutrition, and pneumonia requiring mechanical ventilation is feasible and should be considered a viable management strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
1
10
0
2
Order By: Relevance
“…Bhatt et al. suggested that attempts to resolve preoperative respiratory infection completely would not be possible in the presence of significant increased pulmonary blood flow . Patients with CHD awaiting surgery admitted to the PICU in our cohort had high morbidity and mortality depicting a very high risk in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bhatt et al. suggested that attempts to resolve preoperative respiratory infection completely would not be possible in the presence of significant increased pulmonary blood flow . Patients with CHD awaiting surgery admitted to the PICU in our cohort had high morbidity and mortality depicting a very high risk in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…These maneuvers could reduce the inflammatory process and shorten ICU stay. 14 In the authors' study, the CPB time was longer in the pneumonia group, likely because the complex congenital defects required additional surgical repair in this group. Values are presented as median with range presented in parentheses.…”
Section: Discussionmentioning
confidence: 76%
“…For medium to large size ventricular septal defects, due to the presence of moderate to large left to right shunt in infancy, severe pulmonary hypertension usually occured in the early stage, and it is tended to develop recurrent pneumonia, heart failure and In uence children's growth and development, more seriously even life-threatening [5,6] . For these children pulmonary infection and heart failure that are di cult to control, the longer the course of disease, the more severe the in ammatory injury of lung tissue,and the more di cult the recovery after surgery.…”
Section: Discussionmentioning
confidence: 99%